Erdheim-Chester disease. An important differential diagnosis and its main symptoms - Knitza, Johannes; Kampylafka, E.; Wacker, J.; Schett, Georg; Manger, Bernhard (Zeitschrift für Rheumatologie, 2019)
BackgroundDuring the last 3 years 4 patients were admitted to this hospital with a wide variety of different symptoms, in whom Erdheim-Chester disease (ECD) was diagnosed via different diagnostic pathways.ObjectiveBased on four clinical cases of ECD and using additional information from the literature, this article presents the symptoms of ECD. Furthermore, similarities and differences in comparison to important rheumatological differential diagnoses are presented.ResultsThe ECD is amulti-organ orphan disease. Typical for the disease are long bone involvement, periarterial inflammation especially of the aorta, retroperitoneal and perirenal fibrosis with so-called hairy kidneys in abdominal computed tomography (CT) scans. Treatment is increasingly directed towards the presence of a BRAF mutation, which enables targeted and effective treatment with BRAF inhibitors.ConclusionThe ECD is arare differential diagnosis to rheumatic diseases that causes various and often nonspecific symptoms. Due to modern diagnostic methods with imaging procedures and biopsies it is possible to establish aprecise diagnosis and provide a targeted and effective treatment.
CRIS-Team WoS Importer:2019-02-21